2010
DOI: 10.1111/j.1440-1746.2010.06325.x
|View full text |Cite
|
Sign up to set email alerts
|

Spleen stiffness measurement using fibroscan for the noninvasive assessment of esophageal varices in liver cirrhosis patients

Abstract: Spleen stiffness can be assessed using transient elastography, its value increasing as the liver disease progresses. In liver cirrhosis patients spleen stiffness can predict the presence, but not the grade of esophageal varices. Esophageal varices' presence can be better predicted if both spleen and liver stiffness measurements are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
163
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(177 citation statements)
references
References 29 publications
11
163
2
1
Order By: Relevance
“…As reported, spleen stiffness estimated by real-time elastography, 10 FibroScan, 11 and Virtual Touch tissue quantification (VTQ; Siemens Medical Solutions, Mountain View, CA) on acoustic radiation force impulse imaging [12][13][14][15] can be used for diagnosis of liver fibrosis and portal hypertension and for predicting variceal bleeding. The novel ultrasound-based acoustic radiation force impulse imaging directly estimates tissue stiffness by measuring the speed of shear wave propagation through the tissue in the region of interest (eg, the spleen).…”
mentioning
confidence: 99%
“…As reported, spleen stiffness estimated by real-time elastography, 10 FibroScan, 11 and Virtual Touch tissue quantification (VTQ; Siemens Medical Solutions, Mountain View, CA) on acoustic radiation force impulse imaging [12][13][14][15] can be used for diagnosis of liver fibrosis and portal hypertension and for predicting variceal bleeding. The novel ultrasound-based acoustic radiation force impulse imaging directly estimates tissue stiffness by measuring the speed of shear wave propagation through the tissue in the region of interest (eg, the spleen).…”
mentioning
confidence: 99%
“…Liver cirrhosis is the end stage of chronic liver diseases and a kind of severe and irreversible liver disease, especially when decompensate patients suffer from persistent jaundice, refractory ascites, persistent or obviously delayed prothrombin time, and show complications, all prognoses are relatively poor [3]. Currently, there is still a lack of reliable specific therapy for liver cirrhosis, and the treatment emphasizes etiology and general symptomatic treatment to alleviate the condition, extend the compensated stage and maintain the labor force [4].…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis of 12 studies with 1,497 patients found suboptimal diagnostic accuracy of spleen stiffness measurement (SSM) in the detection of oesophageal varices, with a sensitivity and specificity of <80% [29]. Nevertheless, by using both LSM and SSM Stefanescu et al were able to predict the presence of oesophageal varices with accuracy of 89.95% [30]. Recent meta-analysis, which included 16 studies involving 1,892 patients undergoing LSM and SSM, reported a better overall diagnostic accuracy of SSM, compared with LSM, in the diagnosis of the presence (any grade) of oesophageal varices (AUROC 0.88 vs. 0.81, p<0.01).…”
Section: Spleen Elastography In Portal Hypertensionmentioning
confidence: 99%